Application of Organizational Culture at the Civil Service Police Unit - Rusni Djafar; Umar Sune (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This study aims to explore the implementation of organizational culture at the Office of the Civil Service Police Unit in Pohuwato Regency.  This study was conducted at the Office of the Civil Service Police Unit in Pohuwato Regency. It was employed a qualitative descriptive study. The results shows that organizational culture in the Civil Service Police Unit of Pohuwato regencies based on seven characteristics of organizational culture has shown differences in each characteristic. The strength of organizational culture is seen in four characteristics, namely innovation and risk-taking, attention to detail, results orientation, and individual orientation. Three characteristics, namely team orientation, aggressiveness, and stability, are still not implemented properly. It is also found that work activities are organized into teams rather than individuals, but conflicts are still found in the formed work teams. On the characteristics of aggressiveness, the culture developed has encouraged employees to act aggressively in order to achieve optimal work results, but there are still members of the organization who do not understand the goals, vision, and mission of the aforementioned office. In terms of stability characteristics, technological developments in addition to having an impact on the development of the office, also often bring instability in the office environment.